Towards 1/N Corrections to Deep Inelastic Scattering from the Gauge/Gravity Duality - Jorrin, David Gustavo (2016)
1/N2 corrections to deep inelastic scattering (DIS) of charged leptons from glueballs at strong coupling are investigated in the framework of the gauge/gravity duality. The structure functions F1 and F2 (and also FL) are studied at subleading order in the 1/N2 expansion, in terms of q2 and the Bjorken parameter x. The relevant type IIB supergravity one-loop diagrams (which correspond to DIS with two-hadron final states) are studied in detail, while n-loop diagrams (corresponding to DIS with (n + 1)-hadron final states) are briefly discussed. The 1/N2n and Λ2/q2 dependence of the structure functions is analyzed. Within this context two very different limits are considered: one is the large N limit and the other one is when the virtual photon momentum transfer q is much larger than the infrared confining scale Λ. These limits do not commute.